Propuesta de un Sistema de Abastecimiento JIT para la elaboración del producto Pego Ya en la empresa Dispeco SAS (2021)
This degree project arose due to a need in the company DISPECO SAS, which urgently needs to improve and optimize its internal processes in the elaboration of the paste now product, who intends to seek greater utility, producing what is needed at the moment in which it is need, reducing unnecessary elements without affecting the quality of the product and service. It was possible to build an improvement plan by applying the just-in-time method through tools and techniques that generated strategies to optimize the supply system in the production of the paste now product, which led to improving the quality of the service in the company. To achieve this objective, the tools and techniques to be used for the analysis of the improvement plan were designed, which consisted of interviews with the managerial and operational staff, and the elaboration of a diagnosis through a SWOT matrix and the Ishikawa diagram ( Fish bone), which allowed us to delve a little more into the problem, which allowed us to identify the factors that influence the current condition for the production of the paste already product. Finally, strategies were proposed through a planning and control system, which led to the application of the just-intime method in the company DISPECO SAS, which will allow it to optimize productivity and the effectiveness of the product sticks now